KARAKTERISTIK KARKAS AYAM KAMPUNG UNGGUL BALITBANGTAN (KUB) DENGAN PEMBERIAN FITOBIOTIK EKSTRAK KUNYIT MELALUI AIR MINUM - Ayuningtyas, Gilang; Lestari, Fitriani Eka Puji; Priyambodo, Danang; Sembada, Pria; Wijayanti, Nur Aini (Faculty of Animal Husbandry, University of Mataram, 2025)
This study aims to investigate the effect of the use of phytobiotic from turmeric extract and its combination with probiotics in the drinking water of KUB (kampung unggul Batilbantan) chickens on the characteristics of their carcasses, including their physical and nutritional characteristics. This study involved 24 randomly selected KUB chickens raised for 10 weeks. The treatment were P0 = control drinking water, P1 = Administration of powdered turmeric extract on Monday, Wednesday and Friday, P2 = Administration of powdered turmeric extract on Monday, Wednesday, Friday and probiotics on Tuesday, Thursday and Saturday. The dose of turmeric extract used in each treatment was the same, was 0.5 g/L of drinking water, while the dose of probiotics was 1 ml/L of water. The study used a completely randomized design with three levels of treatment and two replications in each treatment. The variables observed were carcass weight and percentage, percentage of commercial cuts, nutrient content and antibiotic tests on meat. The results of the study showed that the administration of phytobiotics in the drinking water program of KUB chicken was not significantly different (P>0.05) in relation to the observed variables.